THE EFFECT OF DIGITALIZATION ON FOREIGN TRADE AND PAPERLESS FOREIGN TRADE - CORA, Çağla Rahşan; UNCUOĞLU YOLCU, İlknur (Atlas Journal, 2022)
Errors in the documentation that prevent foreign trade, improper document storage, slow payments, and document transfers cause high costs. The cost of the international trading system has allowed banks and companies to explore how their trading processes can be digitized. The emergence of digital technologies with Industry 4.0 makes foreign trade faster and easier. Digital technologies create an opportunity for foreign trade to develop at a qualitatively new level, and in return, foreign trade provides the spread of digital technologies to the world. While digitalization accelerates and simplifies important business processes in international trade and saves all kinds of costs, on the other hand, it transforms traditional forms and models and fundamentally changes the communication system between foreign trade participants. Another important development that Industry 4.0 has had a positive effect on foreign trade is Blockchain technology. By enabling the secure, transparent and immutable sharing of digital records and information without relying on a single trusted third party, Blockchain can empower individuals and companies around the world to conduct transactions more efficiently, economically and quickly, while providing a high level of security. It can have a significant impact on the way trade operations are run, down to physical cross-border trade transactions, thereby reducing processing, verification, monitoring, coordination, and shipping costs by digitizing trade processes. Organizations trying to digitize their paper-based processes are not focusing on the actual elimination of paper but instead on improving their processes, which is expected to bring greater efficiency while bringing greater efficiency at the same time. Paperless foreign trade, which refers to the digitalization of paper-based processes, simplifies the exchange of necessary documents or contract elements, facilitating the flow of information in global supply chains In this context, the aim of the study is to examine the effect of digitalization, which emerged with the Industry 4.0 revolution, on foreign trade.